The three faces of caliphatism: ideas of the caliphate among islamic thinkers of the late 19th - early 20th centuries - Svetlana A. Kirillina; Alexandra L. Safronova; Vladimir V. Orlov (RUDN Journal of World History, 2025)
The study undertakes a rigorous examination of the process of shaping the image of the caliphate and caliphal institutions in the central and peripheral regions of Islamic world in the late 19th century and the first third of the 20th century. To this end, it provides a look at specific examples of creative and political thought, drawing upon the works of prominent Muslim intellectuals and ideologists - Abd al-Rahman al-Kawakibi (1855-1902), Abd al-Aziz Javish (1876-1929) and Abul Kalam Azad (1888-1958). The Ottoman Empire decline accompanied by successful colonization of Muslim lands by Europeans compelled Arab, Turkish, and Indian thinkers to refer to the Ottomans’ experience in the caliphal capacity. Discussions around the duties of the Caliph and conditions for his legitimacy raised a wide range of political, cultural, and philosophical issues. They revealed contradictions in the interpretation of unity within Muslim community (umma), on the question on whether the caliphate and the secular model of social development could coexist, and on the prospects of overcoming the dependence of Muslim peoples on foreign colonial powers. The study sheds light on generational and regional features in the way Muslim intellectual elite regarded the tasks and legitimacy of the rule of the last Ottoman sultans. It reveals historical arguments and ideological attitudes of those who supported and opposed the concept of the ‘Arab caliphate’ (‘caliphate of the Quraysh’), while the concept itself is evaluated in the light of geopolitical change that followed the Young Turk revolution of 1908-1909 and the Ottoman decline after the First World War. This study makes it possible to question the widespread view of caliphatism as a comparatively systematic, logically sound and non-evolving worldview system.